2021
DOI: 10.1155/2021/6663502
|View full text |Cite
|
Sign up to set email alerts
|

Compact Stars Admitting Noether Symmetries in Energy-Momentum Squared Gravity

Abstract: This paper investigates the geometry of compact stellar objects through the Noether symmetry approach in the energy-momentum squared gravity. This newly developed theory overcomes the problems of big bang singularity and provides the viable cosmological consequences in the early time universe. Moreover, its implications occur in high curvature regime where the deviations of energy-momentum squared gravity from general relativity is confirmed. We consider the minimal coupling model of this modified theory and f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 28 publications
(2 citation statements)
references
References 63 publications
0
2
0
Order By: Relevance
“…Shamir and Naz [68] considered the Noether symmetry approach to examine the stability of anisotropic stellar structures in modified f  ( )gravity. We have further extended this work in modified f T ,  ( ) [69] and f T , 2  ( ) [70] theories and found that the obtained solutions depict the viability of proposed Noether symmetric scheme. Azmat and Zubair [71] employed a gravitational decoupling approach to study the geometry of PSR J1614-2230, PSR 1937 + 21 and SAXJ1808.4-3658 compact stars in this theory.…”
Section: Literature Reviewmentioning
confidence: 70%
“…Shamir and Naz [68] considered the Noether symmetry approach to examine the stability of anisotropic stellar structures in modified f  ( )gravity. We have further extended this work in modified f T ,  ( ) [69] and f T , 2  ( ) [70] theories and found that the obtained solutions depict the viability of proposed Noether symmetric scheme. Azmat and Zubair [71] employed a gravitational decoupling approach to study the geometry of PSR J1614-2230, PSR 1937 + 21 and SAXJ1808.4-3658 compact stars in this theory.…”
Section: Literature Reviewmentioning
confidence: 70%
“…A number of research work in relativistic astrophysics using Finch-Skea metric has been done in various modified theories [47]- [52]. Sharif and Gul [53] investigated the geometry of compact stars admitting Noether symmetry technique in f (R, T 2 ) theory. They also analyzed the dynamics of gravitational collapse with different matter distributions and concluded that the modified terms reduce the collapse rate [54].…”
Section: Introductionmentioning
confidence: 99%